Advanced electrical engineering - Morton, A. H. (Alexander Hugh) (Pitman Paperbacks, 1968)
This book is divided into three main sections: the first dealing with circuit theory, includes discussion of matrik methods of analysis, the use of the laplace transform for dealing with transient problems and transmission lines, including the application of the Smith chart. The second section is concerned with field theory, and the third with principles of electrical measurements. SI units are used throughout, and many of the examples and problems are taken from past papers of the IEE and London University examinations.